Psycoeducative Family Therapy Mempengaruhi Pengetahuan, Dukungan Keluarga dan Stigma Kusta - Mega Arianti Putri; Harmayetty Harmayetty; Budi Utomo (Universitas Airlangga, 2016)
Introduction: A person with leprosy present disability and lesions caused by related nerve damage. Without treatment leprosy can permanently damage skin, feet and eyes. Leprosy-related documents show that stigma is typically a very deep rooted social process. It refers to unfavourable attitudes and beliefs directed toward someone or something. The stigma against leprosy not only burdens the affected individuals but also their family members. This research aims was to analyze the influence of family on knowledge psychoeducative intervention, family support and the self stigma.Methods: The design was a quasy experiment. The samples were the intervention and the comparison group each of 30 respondents. The sample consisted of respondent and respondent's family. Sampling technique is using purposive sampling. The research instrument was a questionnaire used by researchers.Results: The result showed that not only psychoeducative family influence level of knowledge, support family and self stigma. The other factor are family characteristics and respondent characteristics. The statistical result shown that a significant relationship between psychoeducative family with knowledge (p=0,000), family support (p=0,000) and the stigma of leprosy (p=0,004).Conclusion: Level of knowledge, family support and self stigma have relations to each other. Families who have less knowledge about leprosy will influence to be given family support. Leprosy patients who have high self stigma caused by lack of knowledge and they feel there have not symphaty, attention and support from their families.